Functional Redundancy Facilitates Resilience of Subarctic Phytoplankton Assemblages toward Ocean Acidification and High Irradiance - Hoppe, Clara J. M.; Schuback, Nina; Semeniuk, David M.; Maldonado, Maria T.; Rost, Björn (Frontiers in Marine Science, 2017)
In order to understand how ocean acidification (OA) and enhanced irradiance levels might alter phytoplankton eco-physiology, productivity and species composition, we conducted an incubation experiment with a natural plankton assemblage from sub-surface Subarctic waters (Davis Strait, 63°N). The phytoplankton assemblage was exposed to 380 and 1,000 μatm pCO2 at both 15 and 35% surface irradiance over 2 weeks. The incubations were monitored and characterized in terms of their photo-physiology, biomass stoichiometry, primary production and dominant phytoplankton species. We found that the phytoplankton assemblage exhibited pronounced high-light stress in the first days of the experiment (20–30% reduction in photosynthetic efficiency, Fv/Fm). This stress signal was more pronounced when grown under OA and high light, indicating interactive effects of these environmental variables. Primary production in the high light treatments was reduced by 20% under OA compared to ambient pCO2 levels. Over the course of the experiment, the assemblage fully acclimated to the applied treatments, achieving similar bulk characteristics (e.g., net primary production and elemental stoichiometry) under all conditions. We did, however, observe a pCO2-dependent shift in the dominant diatom species, with Pseudonitzschia sp. dominating under low and Fragilariopsis sp. under high pCO2 levels. Our results indicate an unexpectedly high level of resilience of Subarctic phytoplankton to OA and enhanced irradiance levels. The co-occurring shift in dominant species suggests functional redundancy to be an important, but so-far largely overlooked mechanism for resilience toward climate change.